2019
DOI: 10.1515/epoly-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Development of vegetable oil-based conducting rigid PU foam

Abstract: In this study, carbon fibre powder has been used as reinforcement to enhance the electrical conductivity of bio-based rigid polyurethane foam. Effect of carbon fibre incorporation on the mechanical, thermal and flame retardant properties has also been investigated. Results concluded that the foams with 8% carbon fibre concentration showed up to 288% increase in compressive strength. Furthermore, up to 28% decrease in the peak of heat release rate (PHRR) was observed on the incorporation of carbon fibre powder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The scientific works focused on environmentally-friendly substrates used for the polyurethane production are actually related with bio-based polyols, bioglycols and the methods of their synthesis [ 1 8 ]. However, in the case of bio-based isocyanates or more environment-friendly methods of PU production are not so common [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific works focused on environmentally-friendly substrates used for the polyurethane production are actually related with bio-based polyols, bioglycols and the methods of their synthesis [ 1 8 ]. However, in the case of bio-based isocyanates or more environment-friendly methods of PU production are not so common [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RPUFs developed in the given study have been derived from a plant source i.e. castor oil, the properties of which are studied and reported earlier by the some researchers [20][21][22][23][24][25][26][27] and other investigators and found to be comparable with commercial petrochemical based RPUFs.…”
Section: Introductionmentioning
confidence: 75%
“…The RPUF composites were obtained by the same method as reported in the literature, in brief, modified polyol is prepared by the transesterification of castor oil under the atmosphere of nitrogen using 2:1 ratio of castor oil to glycerol at the temperature 180–200 °C for 4 h to attain the hydroxyl value of 350–450 mg KOH equiv g −1 . The number average molecular weight of the modified polyol was determined using gel permeation chromatography and recorded as 1165 g/mol.…”
Section: Methodsmentioning
confidence: 99%